2003
DOI: 10.1074/jbc.m307562200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Lipoprotein Initiating Domain of Apolipoprotein B

Abstract: We have explored the minimum sequence requirement for the initiation of apolipoprotein B (apoB)-mediated triglyceride-rich lipoprotein assembly. A series of apoB COOH-terminal truncation mutants, spanning a range from apoB34 (amino acid residues 1-1544 of apoB100) to apoB19 (residues 1-862) were transfected into COS cells with and without coexpression of the microsomal triglyceride transfer protein (MTP). ApoB34, -25, -23, -21, -20.5, and -20.1 underwent efficient conversion to buoyant lipoproteins when coexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
4

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(95 citation statements)
references
References 40 publications
4
87
4
Order By: Relevance
“…Our results supported a model in which the first 1000 amino acid residues of apoB are competent to complete the lipid pocket without a structural requirement for MTP, and that this lipid pocket has a fixed lipid capacity on the order of 50 phospholipids (PL) for a total stoichiometry of 70 lipid molecules, a number in close agreement with that reported for the LV complex (29 -31). We propose that the initiation complex in the assembly of apoB-containing lipoprotein particle is PL-rich suggesting a small bilayer type organization rather than a TAG-rich emulsion proposed by others (32). Although our results (27,28) demonstrated that MTP is not a structural requirement for the formation of the lipid pocket, they did not rule out its potential functional role, i.e.…”
Section: * This Work Was Supported By the National Institutes Of Healcontrasting
confidence: 49%
“…Our results supported a model in which the first 1000 amino acid residues of apoB are competent to complete the lipid pocket without a structural requirement for MTP, and that this lipid pocket has a fixed lipid capacity on the order of 50 phospholipids (PL) for a total stoichiometry of 70 lipid molecules, a number in close agreement with that reported for the LV complex (29 -31). We propose that the initiation complex in the assembly of apoB-containing lipoprotein particle is PL-rich suggesting a small bilayer type organization rather than a TAG-rich emulsion proposed by others (32). Although our results (27,28) demonstrated that MTP is not a structural requirement for the formation of the lipid pocket, they did not rule out its potential functional role, i.e.…”
Section: * This Work Was Supported By the National Institutes Of Healcontrasting
confidence: 49%
“…As a positive control, apoB20.1 was analyzed. This form of apoB was shown previously to form a small emulsion particle with a density of ϳ1.24 g/ml when coexpressed with MTP (24). Under the same conditions used for the Vtg analysis, MTP coexpression converted ϳ20% of the total secreted apoB20.1 into a form that floated at d Ͻ 1.25 g/ml (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…To explore whether MTP-mediated stimulation of Vtg secretion is accompanied by its acquisition of lipid, equilibrium density gradient centrifugation at d ϭ 1.25 g/ml KBr was performed as described (24). Vtg recovered from AP-or MTPtransfected cells was recovered in the d Ͼ 1.25 g/ml, lipid-poor bottom gradient fraction (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the exact length required for apoB to form a lipoprotein is still under debate (26,27,31), these seemingly inconsistent observations might reflect an intrinsic property of apoB during the assembly of apoB-containing lipoproteins. There may be flexibility in the assembly of these lipoproteins in response to the environment, in particular the lipid profile and MTP availability.…”
Section: Discussionmentioning
confidence: 99%